Kadınların siyasal öğrenme deneyimleri: KA.DER eğitimi - Perihan TUTAR (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this research is to determine the dynamics of participation of the training, expectations and educational acquirements of women who participated in the Project of the ’Empowerment of Women Citizens’’ conducted by KADER in the context of gender issue. The sample of the research is composed of 23 women who participated in the training activity. The research data was optained with qualitative methods and the interviews were conducted with the sample group by using the interview form developed by researcher. As a result of the study, it has been found that the participants experienced critical learning about gender mainstreaming and the practice to overcome the ideas that blocked women for political participation. The participants remarked that the training activities provide courage, self reliance and motivation for women and contribute to raising awareness among women for political participation